Prognostic value of immunosuppression scores in patients with esophageal squamous cell carcinoma: a multicenter study - Xu, Shao-jun; Luo, Yun-fan; Huang, Jin; Tu, Jia-hua; Chen, Chao; Shen, Yan-ming; Sun, Zhao-min; Chen, Shu-chen (Frontiers in Immunology, 2025)
IntroductionThe prognostic impact of human leukocyte antigen-E (HLA-E) expression and the proportion of natural killer (NK) cells in esophageal squamous cell carcinoma (ESCC) was investigated.MethodsThis study retrospectively evaluated 397 ESCC patients across two centers. The cumulative incidence of recurrence (CIR) and the incidence of tumor-related death (CID) were analyzed in various groups. An immunosuppression score (ISS) was developed based on HLA-E expression and NK cell proportion. Differences between groups were adjusted using inverse probability treatment weighting (IPTW). The factors influencing cancer-specific survival (CSS) and recurrence-free survival (RFS) were also examined.ResultsPatients with low HLA-E expression had significantly higher five-year CIR and CID compared to those with high expression (CIR: 20.7% vs. 45.1%, CID: 19.3% vs. 40.1%; p< 0.001). Similarly, NK cell-positive patients had significantly better five-year CIR and CID than NK cell-negative patients (CIR: 16.3% vs. 59.6%, CID: 13.9% vs. 53.7%; p < 0.001). The Sankey diagram indicated that the low ISS group had a lower recurrence and tumor-related mortality rate (p < 0.05). After IPTW adjustment, the low ISS group showed improved five-year RFS (80.1% vs. 35.4%, p < 0.001) and five-year CSS (82.3% vs. 42.5%, p < 0.001) compared to the high ISS group.ConclusionsESCC with different ISS statuses represents two distinct biological subtypes, underscoring the need for personalized treatment strategies tailored to varying tumor behaviors.